Age estimation in the living: Transition analysis on developing third molars. (December 2015) - Tangmose, Sara; Thevissen, Patrick; Lynnerup, Niels; Willems, Guy; Boldsen, Jesper
Abstract: A radiographic assessment of third molar development is essential for differentiating between juveniles and adolescents in forensic age estimations. As the developmental stages of third molars are highly correlated, age estimates based on a combination of a full set of third molar scores are statistically complicated. Transition analysis (TA) is a statistical method developed for estimating age at death in skeletons, which combines several correlated developmental traits into one age estimate including a 95% prediction interval. The aim of this study was to evaluate the performance of TA in the living on a full set of third molar scores. A cross sectional sample of 854 panoramic radiographs, homogenously distributed by sex and age (15.0–24.0 years), were randomly split in two; a reference sample for obtaining age estimates including a 95% prediction interval according to TA; and a validation sample to test the age estimates against actual age. The mean inaccuracy of the age estimates was 1.82 years (±1.35) in males and 1.81 years (±1.44) in females. The mean bias was 0.55 years (±2.20) in males and 0.31 years (±2.30) in females. Of the actual ages, 93.7% of the males and 95.9% of the females (validation sample) fell within the 95% prediction interval. Moreover, at a sensitivity and specificity of 0.824 and 0.937 in males and 0.814 and 0.827 in females, TA performs well in differentiating between being a minor as opposed to an adult. Although accuracy does not outperform other methods, TA provides unbiased age estimates which minimize the risk of wrongly estimating minors as adults. Furthermore, when corrected ad hoc, TA produces appropriate prediction intervals. As TA allows expansion with additional traits, i.e. stages of development of the left hand-wrist and the clavicle, it has a great potential for future more accurate and reproducible age estimates, including an estimated probability of having attained the legal age limit of 18 years.